Rapid evolution of T2/S-RNase genes in Fragaria linked to multiple transitions from self-incompatibility to self-compatibility - Wu Chen; Hong Wan; Fang Liu; Haiyuan Du; Chengjun Zhang; Weishu Fan; Andan Zhu (Plant Diversity, 2023)
The T2/RNase gene family is widespread in eukaryotes, and particular members of this family play critical roles in the gametophytic self-incompatibility (GSI) system in plants. Wild diploid strawberry (Fragaria) species have diversified their sexual systems via self-incompatible and self-compatible traits, yet how these traits evolved in Fragaria remains elusive. By integrating the published and de novo assembled genomes and the newly generated RNA-seq data, members of the RNase T2 gene family were systematically identified in six Fragaria species, including three self-incompatible species (Fragaria nipponica, Fragaria nubicola, and Fragaria viridis) and three self-compatible species (Fragaria nilgerrensis, Fragaria vesca, and Fragaria iinumae). In total, 115 RNase T2 genes were identified in the six Fragaria genomes and can be classified into three classes (I–III) according to phylogenetic analysis. The identified RNase T2 genes could be divided into 22 homologous gene sets according to amino acid sequence similarity and phylogenetic and syntenic relationships. We found that extensive gene loss and pseudogenization coupled with small-scale duplications mainly accounted for variations in the RNase T2 gene numbers in Fragaria. Multiple copies of homologous genes were mainly generated from tandem and segmental duplication events. Furthermore, we newly identified five S-RNase genes in three self-incompatible Fragaria genomes, including two in F. nipponica, two in F. viridis, and one in F. nubicola, which fit for typical features of a pistil determinant, including highly pistil-specific expression, highly polymorphic proteins and alkaline isoelectric point (pI), while no S-RNase genes were found in all three self-compatible Fragaria species. Surprisingly, these T2/S-RNase genes contain at least one large intron (>10 kb). This study revealed that the rapid evolution of T2/S-RNase genes within the Fragaria genus could be associated with its sexual mode, and repeated evolution of the self-compatible traits in Fragaria was convergent via losses of S-RNase.